A New Class of Low-Loss High-Linearity Electronically Reconfigurable Microwave Filter - Wong, Peng Wen (IEEE, 2008)
A novel electronically reconfigurable microwave bandpass filter based on a switched delay-line approach is presented. In contrast to conventional tunable filters, the approach enables the lossy and nonlinear switching elements to be used as part of the coupling elements rather than within the resonators. Therefore, the filter distinguishes itself through its ability to provide a wide tuning bandwidth with low passband loss and high linearity. Theoretical analysis of the approach is presented in this paper. The feasibility of the approach has been experimentally verified with microstrip circuit prototypes. The filter produced a maximum passband loss of 1.7 dB and a third-order intercept point of >32 dBm with 35% tuning bandwidth.